Treatment of Borneo midstream river water affected by palm oil plantation run-off with sustainable batch electrocoagulation system - Nazeri, Abdul Rahman; Allene, Albania Linus; Calvin, Jose Jol; Siti Noor Linda, Taib; Arif, Parabi; Astisza Syahla Ludmilla, Parabi; Chieng, Kwong Ming; Flora, Lizza Dampan; Ester, Jose Jol; Arzona Bija, James; Airul Azhar, Jitai; Dayang Faidatul Aishah, Abang Abdul Hamid (Elsevier B.V, 2025)
Water degradation from palm oil plantation runoff in Borneo rural areas has compelled the local communities to rely on untreated river water which does not meet the Malaysia National Water Quality Standards. As such, this study aims to design a batch electrocoagulation system to treat midstream river water affected by palm oil plantation run-off water from rural Borneo by utilizing aluminium electrodes. Correspondingly, this study investigates the effect of electric current and residence time on contaminants removal by conducting both water quality and energy operating cost analyses. Subsequent, this study found the optimal reduction in turbidity, colour, and total suspended solids through electrocoagulation treatment is achieved with a high electric current of 5 A and a residence time of 50 min. Besides, the treatment system effectively reduced 99% of turbidity, 99% of colour, and 99% of TSS from Batang Kayan river, while achieving reductions of 97% of turbidity, 98% of colour, and 99% of TSS from the Batang Sadong river. This study has also noticed that the treated levels of turbidity, colour, and TSS in both midstream rivers water meet the Malaysia Class I standard in National Water Quality Standard. From the energy operating cost analysis conducted, the treatment system cost only Ringgit Malaysia (RM) 3.35 or United States Dollars (USD) 0.74 per meter cubic of treated midstream river water. Overall, it is deduced that batch electrocoagulation treatment is deemed effective to treat Borneo midstream river water affected by palm oil plantation run-off by producing water that suitable for domestic consumption at a reasonable cost.